Effect of Differing Durations of High-Intensity Intermittent Activity on Cognitive Function in Adolescents - Lorna M. Hatch (MDPI AG, 2021)
Exercise duration may influence the acute effects on cognition. However, only one study to date has explored the dose-response relationship between exercise duration and cognition in adolescents. Thus, the purpose of this study was to investigate the effect of differing durations of high-intensity intermittent running on cognition in adolescents. Thirty-eight adolescents (23 girls) completed three trials separated by 7 d: 30 min exercise, 60 min exercise, and rest; in a randomised crossover design. The exercise was a modified version of the Loughborough Intermittent Shuttle Test (LIST), which elicited high-intensity intermittent exercise. Cognitive function tests (Stroop test, Sternberg paradigm, Flanker task) were completed 30 min pre, immediately post, and 45 min post exercise. Response times on the incongruent level of the Flanker task improved to a greater extent 45 min following the 30 min LIST, compared to rest (p = 0.009). Moreover, response times improved to a greater extent on the three-item level of Sternberg paradigm 45 min following the 30 min LIST, compared to the 60 min LIST (p = 0.002) and rest (p = 0.013), as well as on the five-item level 45 min following the 30 min LIST, compared to the 60 min LIST (p = 0.002). In conclusion, acute exercise enhanced subsequent cognition in adolescents, but overall, 30 min of high-intensity intermittent running is more favourable to adolescents’ cognition, compared to 60 min.